System Development for Quality Evaluation of Fish Fillet Using Image Processing - Apinai Rerkratn; Anucha Kaewpoonsuk (My University, 2014)
This paper presents system development for quality evaluation of fish fillet using image processing.The proposed system consists of conveyer belt, Ultraviolet (UV) lamp, CCD Camera, electronic circuits, interface card and computer.K-means clustering and thresholding techniques are used for quality evaluation of fish fillet.The image segments are used to calculated area of fish fillet and fish bone.The quality of fish fillet is based on percentage of fish fillet and fish bone area.The experimental results show that the proposed system can evaluate quality of fish fillet.
Keywords: Fillet (mechanics); Fish fillet; Spectroscopy and Chemometric Analyses